Hubungan antara Kecerdasan Emosi dengan Penerimaan Teman Sebaya Pada Remaja di Masa Pandemi Covid-19 - Yusri, Elvida; Herawaty, Yulia (Journal of Islamic and Contemporary Psychology, 2022)
The Covid-19 pandemic has had so many impacts on human life, including the development of adolescents. Adolescents during the Covid-19 pandemic have various problems they must face. The lack of peer acceptance in adolescents during the pandemic causes bored, loneliness, stress, and has an impact on declining academic achievement. One of the factors assumed to be related to peer acceptance is emotional intelligence. The purpose of this study was to determine the relationship between emotional intelligence and peer acceptance in adolescents during the Covid-19 pandemic. The population in this study were adolescents aged 12-19 years with a sample of 100 people obtained by incidental sampling technique. The data collection method uses a modified emotional intelligence scale from Putri (2016) and a peer acceptance scale by Rahmana (2012). Data were analyzed using Spearman’s Rank correlation where the results showed a correlation value of 0.547 with a significance value of 0.000 (p <0.05). It can be concluded that there is a positive and significant relationship between emotional intelligence and peer acceptance in adolescents during the Covid-19 pandemic, meaning that the higher the emotional intelligence, the higher the peer acceptance, on the contrary, the lower the emotional intelligence, the lower the peer acceptance.